Residents’ perspectives: Does the Saudi general surgery residency training program apply CanMEDS competencies and prepare future leaders? (Canadian Medical Education Journal, 2020)
Background: This study investigates leadership skills and Canadian Medical Education Directives for Specialists (CanMEDS) competencies acquisition within the General Surgery Residency Training Program (GSRTP). The Saudi Commission for Health Specialties (SCFHS) incorporates the CanMEDS Competency Framework into its curriculum to prepare the resident for healthcare needs.Methods: This is a descriptive-analytical study. A questionnaire was used to collect data from 117 General Surgery residents (GS) at seven institutes in Jeddah, Saudi Arabia.Results: The GS residents reported an acceptable self-perceived level of Clinical Leadership Skills (mean ± standard deviation). The most dominant skill was working with others (1.98 ± 1.03), followed by demonstrating personal qualities (2.07 ± 0.88), the ability to manage services (2.21 ± 1.37), improving services (2.22 ± 1.84) and last, setting directions (2.39 ± 0.95). Regarding the CanMEDS competencies, the respondents showed a generally positive perception with an “agree” level (Mean = 1.83). Of the CanMEDS competency roles, Collaborator ranked first followed by Professional and then Communicator. Leader competency ranked fourth followed by Health Advocate, Medical Expert and last, Scholar.Conclusion: The GSRTP residents showed satisfactory self-assessed clinical leadership skills and acquirement of the CanMEDS competencies during their training, which will prepare them to lead in the future.